2018
DOI: 10.1088/1367-2630/aaad41
|View full text |Cite
|
Sign up to set email alerts
|

Chaotic signatures of photoconductive Cu2ZnSnS4nanostructures explored by Lorenz attractors

Abstract: Photoconductive and third-order nonlinear optical properties exhibited by Cu 2 ZnSnS 4 nanostructures are presented. The samples were synthetized in thin film form by a spray pyrolysis processing route. Distinctions in the photoconductive behavior throughout the samples were clearly noted by modulating their optoelectronic response dependent on electrical frequency. Vectorial two-wave mixing experiments were carried out at a 532 nm wavelength provided by a Nd:YAG laser system to study the optical nonlinearitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…It has been previously reported that extraction of particular electromagnetic conditions governed by ultrafast functions is mandatory for designing real-time applications [49]. Regulation of nonlinear optical effects is fundamental in quantum experiments [50], and chaotic attractor signals could be also considered for developing multiphotonic devices. The challenge of optical damage by non-invasive techniques is still in progress and it can be considered the monitoring by chaos algorithms in sensors.…”
Section: Resultsmentioning
confidence: 99%
“…It has been previously reported that extraction of particular electromagnetic conditions governed by ultrafast functions is mandatory for designing real-time applications [49]. Regulation of nonlinear optical effects is fundamental in quantum experiments [50], and chaotic attractor signals could be also considered for developing multiphotonic devices. The challenge of optical damage by non-invasive techniques is still in progress and it can be considered the monitoring by chaos algorithms in sensors.…”
Section: Resultsmentioning
confidence: 99%
“…The results could be useful in the study of optical pulse propagation in nonlinear media, espicially, how the nonolinearity effects non dephasing of the optical signal [39]. More importantly, it is important to have an idea of their frequency response to engineer novel schemes for sensing, control, and manipulation of signals, and our analysis will be extremely useful to fulfill that goal as it determines speed while designing and manufacturing ultrafast devices such as photo-sensors [8], storage systems [9] and switching systems [1,6,7]. Based on the performance of the numerical techniques, we conclude by saying that one can consider it to be a promising platform to handle nonlinear systems, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the multistability of nonlinear systems offers a window for a long-range of applications. Starting from first experimentally achieving a bistable state inside a Fabry-Perot optical device cavity [5], it gives immense motivation for the construction of switching elements for potential use in optical communications and computation [1,6,7], nanophotonic devices such as lowdimensional tunable photo-sensors [8], magneto-optical storage devices [9], NRZ-to-RZ conversion [10], regeneration, monitoring, multi-casting, demultiplexing and multiple-wavelength generation [11,12]. This prospect of technological applications demands to have sufficient knowledge of their frequency response, relative phase, and squeezed phase parameters to engineer the performance of the devices and control and manipulation of signals.…”
Section: Introductionmentioning
confidence: 99%
“…The realization of a chaotic circuit has important physical significance for the application of chaos theory [38]. The chaotic circuit can solve the chaotic degradation with the finite precision of a computer.…”
Section: Electronic Circuit Implementationmentioning
confidence: 99%